Clinical Significance of Preoperative Serum High Density Lipoprotein Cholesterol Levels in Soft Tissue Sarcoma. Issue 18 (May 2015) - Que, Yi; Jiang, Feng; Liu, Liting; Li, Yuanfang; Chen, Yongming; Qiu, Haibo; Zhou, Zhiwei; Zhang, Xing; Wilhelm., Mistiaen
<x xml:space="preserve">Abstract</x> Abstract The prognostic value of lipid profile remains unclear in soft tissue sarcoma. The aim of the present study was to validate the prognostic value of preoperative plasma lipid profile (high density lipoprotein-cholesterol [HDL-C], low density lipoprotein-cholesterol [LDL-C], cholesterol, and triglycerides) levels on disease-free survival (DFS) and overall survival (OS) in soft tissue sarcoma (STS) patients undergoing extensive and radical surgical resection. The preoperative plasma lipid profile levels of 234 STS patients, who were operated on between 2000 with 2010, were retrospectively evaluated. Kaplan-Meier curves and multivariate Cox proportional models were calculated for DFS and OS. In univariate analysis, a decreased HDL-C level was significantly associated with decreased OS (hazard ratio [HR], 3.405; 95% confidence interval (CI), 1.445–8.021, P = 0.005) and remained significant in the multivariate analysis (HR, 5.615; 95% CI, 1.243–25.378, P = 0.025). Patients with HDL-C < 1.475 mmol/L showed a median OS of 71 months. In contrast, patients with HDL-C ≥1.475 mmol/L had a median OS of 101 months. In univariate analysis, a decreased HDL-C level was significantly associated with decreased DFS (HR, 2.085; 95% CI, 1.271–3.422, P = 0.004) and remained significant in the multivariate analysis (HR, 1.808; 95% CI, 1.118–2.924, P = 0.016). Patients with HDL-C <1.475 mmol/L presented with a median DFS of 47 months, whereas patients with HDL-C ≥1.475 mmol/L had a median DFS of 78 months. In univariate analysis and multivariate analyses regarding OS and DFS, there was no significant association between the groups in terms of LDL-C, CHO and TG. Our study investigated the potential prognostic utility of preoperative plasma HDL-C levels as an independent factor in STS patients who had undergone radical surgical resection.